Bank financing and corporate governance - Qian, Meijun; Yeung, Bernard Y. (Journal of Corporate Finance, 2015)
Extant literature suggests that bank monitoring improves corporate governance. This paper demonstrates that inefficiency in banking can also significantly reduce the equity capital markets' disciplinary power. Specifically, we show that in an environment in which the banking system is dominated by inefficient state-owned banks, controlling shareholders' tunneling activity is positively associated with firms' bank loan access. This relation is particularly strong in firms with high borrowing capacity, as measured by tangibility, and in regions where the banking industry is severely inefficient. As firms with high tunneling can continue to receive new loans with interest cost compatible to others, equity capital market disciplinary forces do not apply to them. Indeed, we further show that through tunneling, bank financing is negatively associated with future firm performance. These results suggest that, for an economy to develop mature capital markets, it is imperative to improve banking efficiency because its inefficiency dilutes the monitoring role of the market.